2016
DOI: 10.1016/j.ejmech.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antileishmanial activity of C7- and C12-functionalized dehydroabietylamine derivatives

Abstract: Abietane-type diterpenoids, either naturally occurring or synthetic, have shown a wide range of pharmacological actions, including antiprotozoal properties. In this study, we report on the antileishmanial evaluation of a series of (+)-dehydroabietylamine derivatives functionalized at C7 and/or C12. Thus, the activity in vitro against Leishmania infantum, Leishmania donovani, Leishmania amazonensis and Leishmania guyanensis, was studied. Most of the benzamide derivatives showed activities at low micromolar conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 22 publications
(19 reference statements)
1
16
0
Order By: Relevance
“…A clerodane diterpene in L. donovani exhibited caspase‐3/‐7‐like protease activity and genomic DNA fragmentation, induced mitochondrial dysfunction, and caused an oxidative stress‐mediated apoptotic cell death (Kathuria et al ., ), while kaurenoic acid triggered the NLRP12/IL‐1β/cNOS/NO mechanism in Leishmania amazonensis (Miranda et al ., ). A number of promising leishmicidal diterpenes have been reported (Sinha et al ., ; Sairafianpour et al ., ; Lala et al ., ; Habtemariam, ; González et al , ; Fokialakis et al ., ; Brito et al ., ; Suryawanshi et al ., ; Roy et al ., ; Dos Santos et al ., ; Mondal et al ., ; Soares et al ., ; Santos et al ., ; Mothana et al ., ; Moreira et al ., ; Mokoka et al ., ; Falodun et al ., ; Demarchi et al ., ; da Silva et al ., ; Mizuno et al ., ; Lima et al ., ; Dea‐Ayuela et al ., ). However, their mechanisms of action have not been elucidated.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A clerodane diterpene in L. donovani exhibited caspase‐3/‐7‐like protease activity and genomic DNA fragmentation, induced mitochondrial dysfunction, and caused an oxidative stress‐mediated apoptotic cell death (Kathuria et al ., ), while kaurenoic acid triggered the NLRP12/IL‐1β/cNOS/NO mechanism in Leishmania amazonensis (Miranda et al ., ). A number of promising leishmicidal diterpenes have been reported (Sinha et al ., ; Sairafianpour et al ., ; Lala et al ., ; Habtemariam, ; González et al , ; Fokialakis et al ., ; Brito et al ., ; Suryawanshi et al ., ; Roy et al ., ; Dos Santos et al ., ; Mondal et al ., ; Soares et al ., ; Santos et al ., ; Mothana et al ., ; Moreira et al ., ; Mokoka et al ., ; Falodun et al ., ; Demarchi et al ., ; da Silva et al ., ; Mizuno et al ., ; Lima et al ., ; Dea‐Ayuela et al ., ). However, their mechanisms of action have not been elucidated.…”
Section: Resultsmentioning
confidence: 97%
“…In some studies, diterpenes in nanoformulations (Roy et al, 2010;Mondal et al, 2013) as well as their laboratory derivatives have been reported to exhibit promising anti-NTDs activities (Watson and Preedy, 2010;Mander and Liu, 2010). Additionally, a number of diterpenes have been reported to act against multiple strains responsible for a particular NTD (Sanchez et al, 2006;Dea-Ayuela et al, 2016;Johnson et al, 1993;Riel et al, 2002;Clarkson et al, 2003;Kalauni et al, 2006;Ojo-Amaize et al, 2007;Wangchuk et al, 2010;González et al, 2014;Namukobe et al, 2015;Liu et al, 1997;Prabu et al, 2015;Encarnación-Dimayuga et al, 2006;Rijo et al, 2010;Arai et al, 2014;Xu et al, 2014a;Xu et al, 2014b) and NTDs (Schmidt et al, 2011;Al Musayeib et al, 2014;Ramírez-Macías et al, 2012;Mothana et al, 2014;Falodun et al, 2014;Mizuno et al, 2015;Mongkolvisut and Sutthivaiyakit, 2007;Rangkaew et al, 2009;Ospina and Rodríguez, 2009;Lekphrom et al, 2010;Almutairi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania species (L. infantum, L. donovani, L. amazonensis and L. guyanensis), as well as for cytotoxicity against J774 macrophages following established procedures. 28 The results on extracellular forms (promastigotes)…”
Section: Gabaa Receptor Modulating Activitymentioning
confidence: 99%
“…It has been reported that furan ring structures can participate in benzoxazine crosslinking reactions and improve the crosslinking density of the system . Dehydroabietylamine is widely used in the fields of dyes, coatings, photochemical resolution, metal processing, and other fine processing . Recently, our group also successfully synthesized two fully bio‐based benzoxazines using dehydroabietylamine .…”
Section: Introductionmentioning
confidence: 99%
“…30,[34][35][36][37] Dehydroabietylamine is widely used in the fields of dyes, coatings, photochemical resolution, metal processing, and other fine processing. [38][39][40][41][42][43] Recently, our group also successfully synthesized two fully bio-based benzoxazines using dehydroabietylamine. 44 This is also the first application of dehydroabietylamine in the field of benzoxazine research.…”
Section: Introductionmentioning
confidence: 99%